2021
DOI: 10.1029/2020sw002557
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Pulsations Driving Geomagnetically Induced Currents

Abstract: Geomagnetically induced currents (GICs) are driven by the geoelectric field induced by fluctuations of Earth's magnetic field. Drivers of intense GICs are often associated with large impulsive events such as coronal mass ejections. To a lesser extent fluctuations from regular oscillations of the geomagnetic field, or geomagnetic pulsations, have also been identified as possible drivers of GICs. In this work we show that these low‐frequency pulsations are directly observed in measured GIC data from power networ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 80 publications
1
60
0
Order By: Relevance
“…ULF waves are known to affect magnetospheric dynamics immediately after shock impacts and during magnetic storms, including drift-bounce resonance with charged particles to form storm-time energetic particles (e.g., Menk, 2011;Zong et al, 2012, and (frequency range 7-25 mHz) associated with flow bursts in the magnetotail, Baumjohann and Glassmeier (1984) observed Pi2 pulsations during substorms, and Ngwira et al (2018) observed intense Pc5 (frequency range 1.5-5 mHz) wave activity around the dawn and midnight sectors associated with intense dB/dt variations in these regions. Pc5 pulsations are known to occur during GIC-related events (Heyns et al, 2021;Pulkkinen et al, 2005;Yagova et al, 2021). Therefore, it is expected to observe strong ULF wave activity in the events analyzed in this study.…”
Section: Magnetospheric Ulf Wave Contributions To Ground Db/dt Variationsmentioning
confidence: 87%
“…ULF waves are known to affect magnetospheric dynamics immediately after shock impacts and during magnetic storms, including drift-bounce resonance with charged particles to form storm-time energetic particles (e.g., Menk, 2011;Zong et al, 2012, and (frequency range 7-25 mHz) associated with flow bursts in the magnetotail, Baumjohann and Glassmeier (1984) observed Pi2 pulsations during substorms, and Ngwira et al (2018) observed intense Pc5 (frequency range 1.5-5 mHz) wave activity around the dawn and midnight sectors associated with intense dB/dt variations in these regions. Pc5 pulsations are known to occur during GIC-related events (Heyns et al, 2021;Pulkkinen et al, 2005;Yagova et al, 2021). Therefore, it is expected to observe strong ULF wave activity in the events analyzed in this study.…”
Section: Magnetospheric Ulf Wave Contributions To Ground Db/dt Variationsmentioning
confidence: 87%
“…Indeed, the substantial body of research done on the Hydro Québec blackout in March 1989 and on the impacts of the October 2003 "Halloween" event has identified that fast geomagnetic variations with high amplitude are the ones creating the most severe power system impacts. The specific importance of GIC estimations during SSC has been emphasized by Kappenman (2003Kappenman ( , 2006 and Marshall et al (2012), and the research of GIC during pulsations has been recently presented in Yagova et al (2020) and Heyns et al (2021). Thus, it would be valuable to have further clarification of questions (1) and (2) above.…”
mentioning
confidence: 99%
“…Heyns et al. (2020) presented examples of GIC amplitudes and phases matching closely to the 20‐min period fluctuations of the field (ΔH), which were poorly represented by high‐cadence dB h / dt indicators, while dB h / dt was a better indicator of the rapid field variation that occurred during Sudden Commencements, which often initiate geomagnetic storms. Heyns et al.…”
Section: Introductionmentioning
confidence: 99%